Consumers’ Intention to Adopt m-payment/m-banking: The Role of Their Financial Skills and Digital Literacy - Ullah, Saif; Kiani, Umar Safdar; Raza, Basharat; Mustafa, Abdullah (Frontiers in Psychology, 2022)
The adoption of mobile payment (m-payment) and mobile banking (m-banking) is low in several countries, despite the benefits of m-payment and m-banking. The present study examines the impact of Pakistani consumers’ financial skills and digital literacy on their intention to adopt m-payment/m-banking using the Technology Acceptance Model (TAM). The data were collected from 454 individual smartphone users residing in Punjab province via an online and offline questionnaire survey. Using the structural equation modeling, the results endorse that (1) their financial skills have no association with intention to adopt but through perceived usefulness; (2) their digital literacy bridges a strong association with intention and through perceived ease of use. Furthermore, this study discusses the theoretical and practical implications of the findings, as well as limitations and future directions.